Frequency Of Pseudophakic Glaucoma In A Tertiary Care Hospital Of Pakistan - Fasih, Uzma; Shahid, Erum; Shaikh, Arshad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To evaluate the frequency, causes and management of pseudophakic glaucoma among the pseudophakic patients presenting in a tertiary care hospital of Pakistan. Study Design: Descriptive cross sectional study. Place and Duration of Study: Department of Ophthalmology, Abbasi Shaheed Hospital, Pakistan, from August 2017 to June 2018. Material and Methods: Adult patients between 50 to 70 years of age with pseudophakic glaucoma were included in the study by non-probability convenience sampling after institutional review board approval. Patients with primary open angle, primary angle closure, traumatic glaucoma, diabetes mellitus and hypertension were excluded. Pseudophakic glaucoma was labeled in case of cataract surgery with intraocular lens implantation and intraocular pressure > 21 mmHg or more in one eye along with glaucomatous optic disc or retinal nerve fiber layer defect on OCT (optical coherence tomography). Frequencies were computed for categorical variables. Data was analyzed on SPSS version 20. Results: Twenty-eight eyes with pseudophakic glaucoma were studied. There were 15 (53.57%) males. Mean age was 63 ± 10.4 SD years. Mean IOP was 30.78 ± 7.5 mm Hg. Patients with extracapsular cataract extraction were 18 (64.2%) and 10 (35.8%) had phacoemulsification. Most frequent cause was posterior capsular rupture (n = 16, 57.1%) followed by pupillary block, (n = 4, 14.2%) and UGH (n = 3, 10.7%). Medical treatment was successful in 20 (71.4%) and surgical treatment was done in 8 patients. Conclusion: Most common causes of pseudophakic glaucoma are posterior capsular rupture, vitreous loss, uveitis and pupillary block. Pseudophakic glaucoma is more common with anterior chamber intraocular lenses and extracapsular cataract extraction.